2019
DOI: 10.1111/vec.12920
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive airway pressure (CPAP) provision with a pediatric helmet for treatment of hypoxemic acute respiratory failure in dogs

Abstract: Objective: To evaluate arterial blood gas parameters and pulmonary radiography, before and after provision of continuous positive airway pressure (CPAP) via a pediatric helmet in dogs with acute hypoxemic respiratory failure.Design: Single-center, observational study conducted from 2016 to 2017. Setting: University teaching hospital.Animals: Seventeen dogs presenting with clinical signs compatible with respiratory failure, confirmed by arterial blood gas analyses.Interventions: For each animal arterial blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
1
14
0
3
Order By: Relevance
“…[5][6][7][8] The efficacy of CPAP has been shown in sedated dogs, 8 and in dogs recovering from general anaesthesia or affected by acute respiratory failure. 5,9 Another study showed that 5 cmH 2 O CPAP almost doubled the laryngeal size in anaesthetised dogs using a helmet CPAP device. 10 Similar to other species, sedation or anaesthesia can lead to airway collapse and atelectasis in cats.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The efficacy of CPAP has been shown in sedated dogs, 8 and in dogs recovering from general anaesthesia or affected by acute respiratory failure. 5,9 Another study showed that 5 cmH 2 O CPAP almost doubled the laryngeal size in anaesthetised dogs using a helmet CPAP device. 10 Similar to other species, sedation or anaesthesia can lead to airway collapse and atelectasis in cats.…”
Section: Introductionmentioning
confidence: 99%
“…2014) and in dogs affected by acute respiratory failure (Ceccherini et al . 2020). We found that CPAP restored normoxaemia within 15 minutes of our canine patients with low SpO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…While CPAP is recommended as the first line for ventilatory support of humans with cardiogenic pulmonary oedema, 27 this technique is challenging to adapt to animals. CPAP devices have been tested 33 and applied in canine patients for various pathologies, including canine cardiogenic pulmonary oedema 34 . However, due to patient compliance problems and a lack of experience with these devices in UK veterinary practice, this technique is not in widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…CPAP devices have been tested 33 and applied in canine patients for various pathologies, including canine cardiogenic pulmonary oedema. 34 However, due to patient compliance problems and a lack of experience with these devices in UK veterinary practice, this technique is not in widespread use. As the patient reported here was already anaesthetised and intubated, the decision was made to continue pressure-controlled MV post-operatively, despite the availability of CPAP equipment at our institution.…”
Section: Discussionmentioning
confidence: 99%